Interactional metadiscourse markers in academic research article result and discussion sections - Khedri, Mohsen; Ebrahimi, Seyed Jamal; Chan, Swee Heng (Penerbit Universiti Kebangsaan Malaysia, 2013)
The research article is one of the widely practiced genres of communication among members of academic discourse community to contribute their own new knowledge and get acceptance from the audience. A generic analysis of research articles can cover a wide variety of issues; among them rhetorical features. As argued by Hyland (2004), a valuable means of exploring academic writing and of comparing the rhetorical features and preferences of different discourse communities is through metadiscoursal analysis. Metadiscourse is an aspect of language which provides a link between texts and disciplinary cultures, helping to define the rhetorical context by revealing some of the expectations and understandings of the audience for whom a text is written. Differences in metadiscourse patterns may prove to be an essential means of distinguishing discourse communities (Hyland, 1998). The present paper focused on interactional metadiscourse markers in the result and discussion section of academic research articles across four disciplines, namely, English Language Teaching, Civil Engineering, Biology, and Economics. Sixteen research article result and discussion sections (4 from each discipline) were sourced from four leading international journals for analysis. Results revealed that there were worth-pointing differences, but not statistically significant differences excepting in terms of boosters, between disciplines in the use of interactional metadiscourse markers. Similarities and differences are explained by way of an explication of genre features in terms of contextual configuration and genre specific needs dealing with applied metadiscourse markers by discipline.